The use of communication technologies for the engagement of young adults and adolescents in mental healthcare. (13th September 2011) - Martin, S*; Sutcliffe, P; Griffiths, F; Sturt, J; Powell, J; Adams, A; Dale, J
Abstract : Aims: Examine the use and characteristics of communication technologies by healthcare professionals for the treatment of young people with mental health disorders. Methods: A mixed-method approach was adopted. A synthesis of systematic review and qualitative evidence is presented. Using a rigorous search strategy we searched the peer-reviewed academic literature for studies which either described the use of Information and Communications Technology (ICT) by young people with mental health problems; or evaluated the use of ICT tools for communicating with young people with mental health problems. To capture the views of young people with mental health problems on the use of ICT, we undertook five focus groups with a total of twenty young people. We also identified key organisations and individuals with relevant perspectives and expertise to contribute to our stakeholder interviews. Results: Studies have shown that different interventions have been tested on various platforms, and that in differing contexts both social and clinical benefits are possible. Experimental Studies report statistically significant improvements in symptoms post interventions, while qualitative evidence highlights the acceptability of these technologies and the need for appropriate implementation. Conclusions: Communication technologies can increase the opportunity for communication between patient and healthcare professionals however evidence suggesting improvements in quality of life and continuity of care for patients are limited. Further research exploring best practice, privacy and security is needed. Practice implications: Communication technologies are being used in mental health service delivery, however the impact and effectiveness of these technologies is inconclusive. Researchers and policy makers' need to 'catch-up' with adoption, recognise that the technology by itself is usually not the intervention but simply a platform, and learn from best practice.